Phytochemical and Anti-inflammatory studies on the leaf of Scoparia dulcis Linn (African Journal of Biomedical Research, 2022)
Scoparia dulcis L is a well-known medicinal plant in Nigeria and has many applications in  traditional medicines preparations . Phytochemical screening on the methanol leaf extract of S. dulcis was carried out to identify the phytochemicals present which could be attributed to its acceptability and usage in Nigeria . The extract was also investigated for its anti-inflammatory activity on carrageenan induced paw edema in wistar albino rats .The phytochemical screening of the extract revealed the presence of carbohydrates, tannins, flavonoids, steroids/triterpenes , saponins, cardiac glycosides and alkaloids. The extract at doses of 500 and 1000mg/kg significantly reduced inflammation at the 3rd, 4th and 5th hours  when compared to the control with  a peak inhibition observed  at the 4th hour. The methanol leaf extract of Scoparia dulcis contain bioactive phytochemical with anti-inflammatory activity which explains its use in the treatment of inflammatory conditions in Nigerian traditional medicine.